Analisis Pengaruh Pertumbuhan Penjualan dan Kepemilikan Manajerial terhadap kondisi Financial Distress pada Perusahaan Manufaktur yang ada di Indonesia - Putri, Rita Dwi (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2019)
This study aims to determine the effect of Sales Growth and Managerial Ownership on the condition of Financial Distress in manufacturing companies in Indonesia in 2015-2017. The sample of this study were 13 manufacturing companies listed on the Indonesia Stock Exchange, with a purposive sampling method. Based on the results of statistical analysis by using the t test with the value of t arithmetic equal to -1,249 ? value of t table 2.028 and significance of 0.220 ? from the significance level of 0.05, partially Managerial Ownership does not affect the condition of Financial Distress in the manufacturing company studied. This is proven by using the t test with the value of t count equal to 1.419 19 t table value 2.028 and significance 0.165 ? from the significance level of 0.05. Simultaneously Sales Growth and Managerial Ownership do not affect the condition of Financial Distress in the manufacturing companies studied with F count of 1.789 ? from the value of F table 3.32 and significance of 0.182 ? from the significance level of 0.05. The results of the coefficient of determination of the value of R Square are obtained at 0.090 or 9%. This means that the independent variables namely Sales Growth (X1) and Managerial Ownership (X2) have an influence on the dependent variable, namely the Financial Distress (Y) condition of 9% while the remaining 91% is influenced by other variables.